Right Ventricular Diastolic Performance in Patients With Chronic Thromboembolic Pulmonary Hypertension Assessed by Echocardiography - Meng, Hong; Song, Wu; Liu, Sheng; Hsi, David; Wan, Lin-Yuan; Li, Hui; Zheng, Shan-shan; Wang, Zhi-wei; Ren, Rong; Yang, Wei-xian (Frontiers in Cardiovascular Medicine, 2021)
Background: There have been no systemic studies about right heart filling pressure and right ventricular (RV) distensibility in patients with chronic thromboembolic pulmonary artery hypertension (CTEPH). Therefore, we aimed to explore combinations of echocardiographic indices to assess the stages of RV diastolic function. Methods and Results: We recruited 32 healthy volunteers and 71 CTEPH patients. All participants underwent echocardiography, cardiac catheterization (in CTEPH patients), and a 6-minute walk test (6MWT). Right atrial (RA) end-systolic area was adjusted for body surface area (indexed RA area). RV global longitudinal diastolic strain rates (SRs) and RV ejection fraction were measured by speckle tracking and three-dimensional echocardiography, respectively. All 71 CTEPH patients underwent pulmonary endarterectomy. Of the 71 patients, 52 (73%) had decreased RV systolic function; 12 (16.9%), 26 (36.6%), and 33 (46.5%) patients had normal RV diastolic pattern, abnormal relaxation (stage 1), and pseudo-normal patterns (stage 2), respectively. The receiver operating characteristic curve analysis showed that the optimal cut-off values of early diastolic SR<0.8 s-1 and indexed RA area>8.8 cm2/BSA had the best accuracy in identifying patients with RV diastolic dysfunction, with 87% sensitivity and 82% specificity. During a mean follow-up of 25.2 months after pulmonary endarterectomy, preoperative indexed RA area was shown as an independent risk factor of the decreased 6MWT distance. Conclusions: Measuring early diastolic strain rate and indexed RA area would be useful in stratifying RV diastolic function.